Effects of Dietary Antioxidant on Performance and Physiological Responses Following Heat Stress in Laying Hens - Felver-Gant, J.N.; Dennis, R.L.; Zhao, J.; Cheng , H.W. (International Journal of Poultry Science, 2014)
Heat stress (HS) causes oxidative damage, increasing mortality and reducing productivity in chickens. The objective of this study was to determine the benefits of antioxidant supplementation in laying hens during HS. Eighty 32-week-old W-36 White Leghorn hens were used in this study. Hens were randomly pair-housed in two adjacent rooms and fed a control diet (CF) or control diet mixed with Agrado Plus Ultra®, an antioxidant, at 160 mg/kg (AF) for two weeks. One room was then subjected to a hot climate (H) (33°C) for 8 days. Physical and physiological data were collected at day 1 and 8 during the treatment. Core body temperature was increased (p<0.0001) and BW (p<0.05) and liver weight (p<0.0001) were reduced in laying hens regardless of treatment. However, compared to its respective controls, the concentrations of heat shock protein 70 (HSP70) were increased in H-AF hens (p< 0.01) but not in H-CF hens (p>0.05) at 8 days during the process of HS. Similarly, HSP70 mRNA expression tended to increase in H-AF hens only (p = 0.09). Heat stress reduced the concentrations of total CO2 and bicarbonate (p<0.05), indicating respiratory alkalosis and decreased vitamin A (p<0.01), vitamin E (p<0.0001) and glutathione peroxidase (p<0.05) concentrations but increased protein carbonyl concentrations (p<0.05), indicating protein oxidative damage. A temperature by feed interaction was observed in the concentrations of partial pressure CO2 (pCO2, p<0.05), superoxide dismutase (SOD, p = 0.06) and protein carbonyl (p = 0.1). Heat stress-caused decreases in pCO2 and SOD and increases in protein carbonyl concentrations were found in control hens but not in AF hens. These results suggest antioxidant supplementation attenuates oxidative stress response in laying hens. These data support the hypothesis that supplemental antioxidants improve hen well-being by reducing HS associated physical and physiological damage.